The Legal Dynamics of the Transfer of Rights Over Undivided Inherited Land and the Legal Consequences on the Validity of the Sale and Purchase Deed - Zulfikar Judge (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study discusses the legal dynamics of the transfer of rights over undivided inherited land and the legal consequences on the validity of the Land Deed Official's (PPAT) Sale and Purchase Deed (AJB). In practice, the sale and purchase of undivided inherited land often leads to legal disputes due to the non-fulfillment of the legal requirements for agreements as stipulated in Article 1320 of the Indonesian Civil Code (KUHPerdata). A literature review of secondary data sources, such as laws, legal literature, and pertinent court rulings, is conducted using a normative research approach. According to the study's findings, contracts for the sale and purchase of undivided inherited land are legally void, thus heirs who incur losses may sue for annulment or seek damages. This study also emphasizes the importance of formal inheritance distribution and the role of the PPAT in ensuring the validity of transactions to prevent future disputes. Alternative dispute resolution through mediation is also considered an effective option for maintaining family relationship